Why are Returns on Swiss Franc Asset so Low? - Peter Kugler; Beatrice Weder (University of Basel, Center of Business and Economics (WWZ), 2005)
As is well known, the uncovered interest rate parity fails in the short run but usually holds in the long run. This paper analyses the long and short run interest rate parity of 10 mayor OECD currencies and finds that there is a long run failure of the uncovered interest rate parity condition for the Swiss Franc. After correcting for exchange rate changes, mean returns on Swiss assets have been significantly lower than in other currencies, an anomaly not found in any other major currency. The long run return differential has been stable over the last 20 years, transitory structural breaks are only found in times of currency turmoil. We suggest that the return anomaly may be due to an insurance premium against very rare catastrophic events, such as a major war. Supporting evidence for this hypothesis comes from two empirical findings: First, we show that the return differential is negatively affected by large unexpected geo-political events. Second we examine historical data on interest rates differentials and show that the abnormally low level of Swiss returns arises after the first world war only.
Keywords: E43; E44; G15; 330